Challenges in material processing and reliability issues in AlGaN/GaN HEMTs on silicon wafers for future RF power electronics & switching applications: A critical review. (15th November 2022) - Ajayan, J.; Nirmal, D.; Mohankumar, P.; Mounika, B.; Bhattacharya, Sandip; Tayal, Shubham; Fletcher, A.S. Augustine
Abstract: In order to handle high power with good thermal stability at RF & microwave frequencies wider bandgap semiconductor based transistors are highly desirable and GaN & AlGaN channel HEMTs (High electron mobility transistors) have become most promising devices for RF power and switching electronic applications due to their unique features such as high 2DEG density, excellent breakdown field, good 2DEG mobility & saturation drift velocity and extremely low ON-resistance. GaN & AlGaN channel HEMTs are widely fabricated on SiC or sapphire wafers, but their low wafer size & high fabrication cost hinder the commercialization of these devices. In recent years, Si-wafers have emerged as a pathway for the commercialization of GaN & AlGaN channel HEMTs due to their large wafer size, low cost fabrication & capability to integrate GaN or AlGaN channel power HEMTs on advanced Si-technology. Therefore, in this article, we critically reviewed the issues that need to be addressed while transferring GaN or AlGaN channel HEMTs on Si-wafers. This article also highlights the popular architectures of GaN & AlGaN channel HEMTs on Si-wafers, techniques for enhancing their breakdown performance such as buffer layer engineering, drain contact technologies & surface passivation, challenges in fabrication and reliability issues such as irradiation & thermal degradations.